2006
DOI: 10.1002/anie.200600493
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Active Catalyst for Suzuki–Miyaura Cross‐Coupling Reactions of Heteroaryl Compounds

Abstract: Unprecedented activity: Catalysts derived from Pd and bulky dialkylphosphinobiaryl ligands are shown to be highly stable and active in Suzuki–Miyaura reactions of heteroaryl halides and heteroaryl boronic acids/esters (e.g., 3‐ or 4‐pyridine, indole, and N‐protected pyrrole derivatives). Furthermore, this catalyst system is not inhibited by the presence of highly basic aminopyridines or aminopyrimidines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
171
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(180 citation statements)
references
References 41 publications
4
171
1
2
Order By: Relevance
“…[2] These phosphines have been used as ligands for gold, [3][4][5][6][7][8][9][10][11] silver, [12] rhodium, [13,14] ruthenium [15][16][17] and copper [18] where they have been shown to impart improvements in reactivity and catalyst stability. It is in reactions catalyzed by palladium, however, that they have had by far the greatest impact including the Sonogashira, [19] Negishi, [20] Hiyama, [21][22][23] Kumada [24] and Suzuki [25][26][27][28][29][30] cross-coupling reactions, Heck reaction, [31][32][33] enolate arylation [34][35][36][37] and allylation, [38] reductive cyclization [39] and etherification, [40][41][42][43] silylation, [44] borylation, [45][46][47] cyanation, [48,…”
Section: Introductionmentioning
confidence: 99%
“…[2] These phosphines have been used as ligands for gold, [3][4][5][6][7][8][9][10][11] silver, [12] rhodium, [13,14] ruthenium [15][16][17] and copper [18] where they have been shown to impart improvements in reactivity and catalyst stability. It is in reactions catalyzed by palladium, however, that they have had by far the greatest impact including the Sonogashira, [19] Negishi, [20] Hiyama, [21][22][23] Kumada [24] and Suzuki [25][26][27][28][29][30] cross-coupling reactions, Heck reaction, [31][32][33] enolate arylation [34][35][36][37] and allylation, [38] reductive cyclization [39] and etherification, [40][41][42][43] silylation, [44] borylation, [45][46][47] cyanation, [48,…”
Section: Introductionmentioning
confidence: 99%
“…The molecular framework of these systems can be easily varied in order to fine-tune the ligand properties. 121 It was shown that the catalysts based on S-Phos were not inhibited in the presence of aminopyridines and aminopyrimidines, 122 as found with earlier ligand systems. 123 Various heterocycles including pyrroles, thiophenes, pyrazines, pyridines, quinozalines, indoles, and quinolines have been successfully employed using these systems.…”
mentioning
confidence: 67%
“…202 Another member of this family of natural products has been obtained by palladium-catalyzed coupling of the boron derivative 100 with a pyrrolyl triflate. 203 This pyrrole boronic acid compound has also been employed in other cross-coupling reactions, 204 including progesterone receptor modulators 205 and the total synthesis of ageladine A. 206 When the boronic acid functionality in the protected pyrrole is desired at C-3, its preparation is achieved generally via a brominationlithiation-borination sequence, a recent example being the synthesis of a N-silyl-protected pyrrol-3-ylboronic acid, which has been employed in the synthesis of conductive electrochromic polymers.…”
Section: Aromatic Five-membered Ringsmentioning
confidence: 99%